The Effect of Information Sharing, Supply Chain Collaboration and Supply Chain Agility on Supply Chain Performance in Food and Beverage SME in the Bogor Region - Hanif, Banu; Santosa, Wahyuningsih (Golden Ratio of Data in Summary, 2024)
This study analyzes the influence of information sharing, supply chain collaboration, and supply chain agility on supply chain performance in the food and beverage industry in the Greater Jakarta area. The main focus of this study is to evaluate the extent to which information sharing practices and collaboration between supply chain partners, as well as the ability of the supply chain to respond to change, affect overall supply chain performance. The method used was a survey with SME respondents in the food and beverage sector. The results showed that information sharing has a significant positive influence on supply chain collaboration and supply chain agility, which in turn improves supply chain performance. This research makes an important contribution to the development of supply chain management theory and practice, particularly in the context of SME in the food and beverage sector.